KSHV transactivator-derived small peptide traps coactivators to attenuate MYC and inhibits leukemia and lymphoma cell growth - Michiko Shimoda (Nature Portfolio, 2021)
Shimoda et al. present evidence that a small functional peptide derived from the KSHV transactivator could be used to target MYC in cancer. The authors find that the peptide attenuates MYC expression, reduces cell proliferation, and selectively kills cancer cells in tissue culture and a xenograft tumor mouse model, by blocking recruitment of coactivator complexes (Nuclear receptor coactivator 2, p300, and SWI/SNF proteins) to the MYC promoter.